Quality of sugar palm sap (Arenga pinnata) from various production centers in West Sumatra, Indonesia - TUTY ANGGRAINI; ASWALDI ANWAR; DINI HERVANI; DEDE SUHENDRA; MUHAMMAD PARIKESIT WISNUBROTO; NOFLINDAWATI NOFLINDAWATI; ILHAM HAMIDI NASUTION (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Anggraini T, Anwar A, Hervani D, Suhendra D, Wisnubroto MP, Noflindawati, Nst IM. 2025. Quality of sugar palm sap (Arenga pinnata) from various production centers in West Sumatra, Indonesia. Biodiversitas 26: 859-860. Arenga pinnata is a palm tree that produces palm sap, which contains high sugar content and offers a sweet taste and bioactive components that function as antioxidants. These A. pinnata trees grow in West Sumatra, where sugar palm fruit and palm sap sugar are the main horticultural products. In this study, we investigated the quality of palm sap (A. pinnata) from various sap-producing regions thrive in West Sumatra, Indonesia, focusing on their color, total sugar contents, antioxidant activities, total phenolic contents, and Fourier Transform Infra-Red (FTIR) measurements. We compared palm sap sugar from the West Pasaman, Agam, Tanah Datar, Limapuluh Kota, South Solok, and Dharmasraya regions in West Sumatra. The color of palm sugar sap is vibrant yellow-red. The total sugar content ranges from 7-15.73%. The antioxidant activity of palm sap varies based on its concentration, with its total polyphenol content ranging from 46.32-499.32 mg GAE/g, highlighting the potential health benefits of palm sap. We also used the FTIR analysis to identify functional groups in the samples. This finding showed that the quality of palm sap found in West Sumatra varies in terms of quality. Based on its antioxidant content, MNJ A has the highest antioxidant activity, and TLM A has the highest total polyphenols. These results show that total polyphenols are not the only ones that contribute to the antioxidant activity of palm sap.